2001
DOI: 10.1029/2000gb001302
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea flux of oxygen estimated from bulk data: Implications For the marine and atmospheric oxygen cycles

Abstract: Abstract. We estimate the annual net air-sea fluxes of oxygen for 13 regions on the basis of a steady state inverse modeling technique that is independent of air-sea gas exchange parameterizations. The inverted data consist of the observed oceanic oxygen concentration after a correction has been applied to account for biological cycling. We find that the tropical oceans (13øS-13øN) emit •212 Tmol 02 yr -•, which is compensated by uptake of 148 Tmol yr -• in the Northern Hemisphere (>13øN) and by uptake of 65 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
172
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 105 publications
(201 citation statements)
references
References 87 publications
20
172
9
Order By: Relevance
“…The Pacific Ocean equatorial APO bulge predicted by Stephens et al [1998] and Gruber et al [2001], and later confirmed from observations by Battle et al [2006] and Tohjima et al [2005b], is not apparent in our Atlantic APO data in 2015. Owing to the development of strong El Niño conditions during 2015, it is possible that the equatorial APO bulge was suppressed by ENSO-related changes in ITCZ position and atmospheric transport, as was found to be the case in the western Pacific Ocean during 2010 [Tohjima et al, 2015].…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…The Pacific Ocean equatorial APO bulge predicted by Stephens et al [1998] and Gruber et al [2001], and later confirmed from observations by Battle et al [2006] and Tohjima et al [2005b], is not apparent in our Atlantic APO data in 2015. Owing to the development of strong El Niño conditions during 2015, it is possible that the equatorial APO bulge was suppressed by ENSO-related changes in ITCZ position and atmospheric transport, as was found to be the case in the western Pacific Ocean during 2010 [Tohjima et al, 2015].…”
Section: Discussionmentioning
confidence: 49%
“…For example, Stephens et al [1998] found that model-generated latitudinal gradients in annual-mean APO over the Pacific Ocean significantly underestimated the observed interhemispheric gradient in APO, suggesting that the models were underestimating the net southward transport of oceanic potential oxygen (the oceanic equivalent of APO [see Resplandy et al, 2016]) in the oceans. A later study by Gruber et al [2001] also found that modeled APO underestimated the observed APO interhemispheric gradient, particularly at southern hemisphere high-latitude stations. However, these authors found that robustly constraining oceanic transport of O 2 and CO 2 using APO data was not possible.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations